Komposisi Musik ‘’Batuk Dalam Hening” - Nurhafitrah, Nanda Qory; Setiaji, Denden (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The process of creating a contemporary musical work "Komposisi Batuk dalam Hening" is discussed in this article. The main sound of the musical composition of this work is considered to be the sound of coughing, which has many values ​​of expression, symbolism, and social criticism. The sound of coughing, which is usually considered a physical symptom or disorder, is elevated into an artistic element that is able to convey emotional nuances, tension, and inner silence of humans through an experimental approach and vocal exploration techniques. This study uses a qualitative descriptive approach, which includes the phases of observation, sound recording, structural exploration, and artistic reflection. The results show that coughing can be a powerful and evocative means of expression if used in the right context and with careful musical arrangement. This work functions as a form of resistance to the limitations of conventional music while emphasizing the relationship between body, voice, and social consciousness in a world that is often too noisy to hear small things.